Headspace control and antimicrobials: Inhibition strategies to prevent the growth of Alicyclobacillus acidoterrestris in orange juice - Gamboa Moreno, Paola María (2022)
Alicyclobacillus acidoterrestris can cause spoilage in orange juice that leads to consumer rejection. Six different orange juices were physiochemically characterized (pH, total soluble solids, titratable acidity, total polyphenols and vitamin C). A bottle for each sampling point per juice was filled (headspace: 40% volume) and inoculated with 102 -103 CFU per ml of A. acidoterrestris ATCC® 49025™ (heat shocked before inoculation: 75°C, 20 min). Samples were stored for 21 days at 45 ± 1°C and plate counted periodically on acidified YSG agar (pH 3·7) incubated at 45 ± 1°C for 3 days. The effect of headspace (6% versus 40% volume) on A. acidoterrestris growth was also evaluated. The effect of nisin (0·006, 0·003, 0·0015, and 0·00075%), sodium benzoate (0·1%), potassium sorbate (0·1%) and a mix of benzoate and sorbate (0·05% each) on A. acidoterrestris was additionally addressed. Alicyclobacillus acidoterrestris reached up to 107 CFU per ml in five of the six juices in less than 1 week. Headspace significantly impacted (P < 0·05) A. acidoterrestris maximum population, which reached the critical value of 5 log CFU per ml at 40% headspace. All preservatives, regardless of concentration, showed a bacteriostatic effect during 22 days of storage with no significant differences amongst treatments (P > 0·05).